The Differences in the Types of Linguistic Games for Foreigners and Native Speakers - Zwolińska, Paulina (Ludicity in (Glotto)Didactic, 2020)
The article presents a comparison of linguistic games teaching Polish to both foreigners and native speakers. Differences result from various methodologies applied while teaching both types of learners. The analysis of linguistic games dedicated to various recipients can exhibit competences emphasized by their authors.